Annotations give meaningful learning experience / Farah Merican Isahak Merican, Nizar Nazrin and Shafilla Subri - Isahak Merican, Farah Merican; Nazrin, Nizar; Subri, Shafilla (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
When possible, we write our annotations on pages as we read. Annotations allow us to underline, jot simple notes, and post or stick notes on the pages. We annotate while reading or after reading. In lectures, educators encourage their students to annotate to activate their learning and to enhance knowledge transfer. Annotations have been proven to be a tool to foster better cognitive development and enhances student learning engagement (Tseng, 2021). Annotations can also be seen as a way for students or lecturers to talk to their own work. Annotations reveal our thinking and personal responses rather than the views of others. It helps to explain relevance and our own connections to the subjects.